TANGGUNG JAWAB PERBUATAN DIREKSI YANG DILAKUKAN ATAS NAMA PERSEROAN TERBATAS YANG BELUM MEMPEROLEH STATUS BADAN HUKUM - Tommy Guntara, I Gede; Palguna, I Dewa Gede (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 01, Februari 2014)
This paper entitled “Legal Responsbility fo Acts of Direktor Carried Out on Behalf of A Limited Company Which Has No Legal Person Status” is a normative legal research. This research is aimed at describing and analizing the legal responsibility for acts carsied out by director on behalf of such a company.
Keywords: Responsibility, Corporation, Limited Company